ANALISIS KUALITAS PELAYANAN JASA, LOKASI DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KEPUASAN PELANGGAN PADA TAHUN 2022-2023 (STUDI KASUS PADA KLINIK MATA EDC WARUJAYENG) - Fauzi, Ahmad; Ratnanto, Sigit (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The purpose of this study is to evaluate the effects of Warujayeng EDC Eye Clinic's service quality, location, and corporate social responsibility on client satisfaction. In terms of sampling, EDC Warujayeng Eye Clinic patients were given questionnaires to fill out. Validity tests, reliability tests, multiple regression analyses, and hypothesis testing were used in the data analysis. The findings indicated a substantial relationship between customer satisfaction with treatment and service quality. Location had a substantial impact on consumer happiness. The impact of corporate social responsibility on customer satisfaction was substantial. administered at the EDC Warujayeng Eye Clinic.